Socio-demographic predictors of obesity among 12,975 adult ever married Egyptian women of reproductive age group: evidence from nationwide survey - Amr Ehab El-Qushayri; Md Anwar Hossain; Imteaz Mahmud; Mohammad Rashidul Hashan; Rajat Das Gupta (BMC, 2023)
Abstract Aim We aimed to explore the predictors associated with obesity among adult ever-married Egyptian women aged 20-49 years based on the Egyptian Demographic and Health Survey (EDHS). Method We included adult ever married women from the EDHS conducted in 2014 that initially recruited 21,903 women. Univariate and multivariable analysis was conducted to identify socio-demographic predictors of women's obesity. Result We included 12,975 Egyptian women. Among them, 76% of the total respondents were obese where as 24% were with normal body mass index (BMI). In multivariable analysis, the results revealed that increasing age, higher wealth index, listening to radio at least once a week and women with primary and secondary education were at significant odds of developing obesity (p < 0.05). However, we found no association between residence of participants and the frequency of watching television upon the development of obesity (p > 0.05). Conclusion Appropriate and targeted interventions should be implemented among the Egyptian reproductive age women to reduce the obesity as well as non-communicable diseases load associated with obesity. National Health Service policy makers should take multilevel approach targeting high risk sub-groups to raise awareness and to provide prevention against obesity and the subsequent complications.